PENGEMBANGAN BAHAN AJAR E-MODUL BERBASIS GOOGLE SITE UNTUK MENINGKATKAN LITERASI GEOGRAFI DAN HASIL BELAJAR SISWA MATERI POSISI STRATEGIS INDONESIA KELAS XI DI SMA NEGERI 1 KEDUNGADEM BOJONEGORO - utami, rita dwi; Muzayanah, Muzayanah; Lestari Sitohang, Lidya (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This study aims to develop Google Sites-based e-module teaching materials to improve geographic literacy and learning outcomes of eleventh-grade students on the topic of Indonesia's Strategic Position at SMA Negeri 1 Kedungadem Bojonegoro. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were students of grades XI-7 as the experimental class using the e-module and grades XI-8 as the control class using varied PPT. The validation results showed that the e-module obtained a score of 86.66 from media experts and 90.13 from material experts, with a very feasible category. The results of the effectiveness test showed a significant increase with an average pre-test score of 54.19 increasing to 84.44 in the post-test. The paired sample t-test produced a significance value of 0.000 (p<0.05), indicating a significant difference between the pre-test and post-test. The N-Gain Score analysis showed a value of 0.6483 or 64.83% which is included in the moderate category. Student response to the e-module was very positive, with 81.8% feeling more engaged in learning and 63.6% understanding the importance of local culture. The Google Sites-based e-module proved effective in improving geographic literacy and student learning outcomes on the topic of Indonesia's Strategic Position.